Analisis Tata Kelola Infrastruktur IT pada Universitas Lahat dengan Menggunakan Metode Framework Cobit 5 - Zulkarnain, Zulkarnain; Kokocaniago, Kokocaniago (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Effective information technology (IT) infrastructure governance is an important factor in supporting the quality of academic and administrative services in higher education institutions. However, the implementation of IT governance in many higher education institutions is still not optimal and is not fully aligned with institutional objectives. This study aims to analyse the level of IT infrastructure governance capabilities at Serelo Lahat University and formulate recommendations for improvement using the COBIT 5 framework. The research method used is a descriptive approach with data collection techniques through observation, interviews, and distribution of questionnaires to relevant parties. The assessment focused on the EDM (Evaluate, Direct, and Monitor) and APO (Align, Plan, and Organise) domains. The results showed that the level of IT governance capability still needed to be improved, particularly in terms of strategic planning and IT risk management. Based on these findings, this study recommends strengthening policies, improving strategic planning, and implementing more structured risk management. These recommendations are expected to help universities optimise IT governance to support more effective academic and administrative services that are adaptive to technological developments.